1998
DOI: 10.1136/bmj.316.7126.189
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal vitamin K administration and childhood cancer in the north of England: retrospective case-control study

Abstract: results are not independent. Those for the present paper, however, are based on more cases, and the method of analysis is entirely different and, in particular, does not use the controls from the other studies. Although (with some minor and possibly questionable exceptions) the results of the present analyses are not significant and there is no suggestion of a doubling of the risk of malignant disease arising from the use of intramuscular vitamin K, the findings for childhood leukaemia are compatible with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“…administration of vitamin K accords with the majority of individual studies to have reported on this topic (Ekelund et al, 1993;Klebanoff et al, 1993;Olsen et al, 1994;Ansell et al, 1996;von Kries et al, 1996;Roman et al, 1997;McKinney et al, 1998;Passmore et al, 1998a, b) and with the results of an individual record-based pooled analysis of the six major case -control studies (Roman et al, 2002). The one exception is a study carried out in the former Northern Health region of England which, although it found no association for all childhood ALL (OR ¼ 1.20, 95% CI ¼ 0.75 -1.92, based on 207 cases), reported a statistically significantly raised OR for ALL diagnosed between 12 and 71 months of age (OR ¼ 1.79, 95% CI ¼ 1.02 -3.15, based on 144 cases) (Parker et al, 1998). To investigate this further, a metaanalysis of the results published by Roman et al (2002) and the results reported here has been undertaken.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…administration of vitamin K accords with the majority of individual studies to have reported on this topic (Ekelund et al, 1993;Klebanoff et al, 1993;Olsen et al, 1994;Ansell et al, 1996;von Kries et al, 1996;Roman et al, 1997;McKinney et al, 1998;Passmore et al, 1998a, b) and with the results of an individual record-based pooled analysis of the six major case -control studies (Roman et al, 2002). The one exception is a study carried out in the former Northern Health region of England which, although it found no association for all childhood ALL (OR ¼ 1.20, 95% CI ¼ 0.75 -1.92, based on 207 cases), reported a statistically significantly raised OR for ALL diagnosed between 12 and 71 months of age (OR ¼ 1.79, 95% CI ¼ 1.02 -3.15, based on 144 cases) (Parker et al, 1998). To investigate this further, a metaanalysis of the results published by Roman et al (2002) and the results reported here has been undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…vitamin K and any diagnostic group, with the pooled OR for ALL diagnosed between 12 and 71 months being: OR ¼ 0.98, 95% CI ¼ 0.79 -1.22 (based on 1201 cases). In light of all the available evidence, the most likely explanation for the finding of Parker et al (1998) would seem to be chance. Accordingly, we conclude that there is no convincing evidence that neonatal vitamin K administration, irrespective of the route by which it is given, influences the risk of children developing leukaemia or any other cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vitamin K prophylaxis became a controversial topic when Golding et al (1992) reported that children who received it by this route were almost three times as likely to develop leukaemia as children who received it orally or not at all. Although subsequent studies failed to confirm these findings (Ekelund et al, 1993;Klebanoff et al, 1993;Olsen et al, 1994;Ansell et al, 1996;von Kries et al, 1996;Roman et al, 1997;McKinney et al, 1998;Parker et al, 1998;Passmore et al, 1998a,b), inconsistencies in their results have left lingering doubts about the safety of I.M. administration (Kaufman, 1999).…”
mentioning
confidence: 99%
“…In order to investigate this topic in more depth, a pooled analysis of individual patient data from the six major case -control studies (Golding et al, 1992;Ansell et al, 1996;von Kries et al, 1996;Roman et al, 1997;McKinney et al, 1998;Parker et al, 1998;Passmore et al, 1998a) has been undertaken. The principal aims were to use consistent definitions of exposure and potential confounders to:…”
mentioning
confidence: 99%